1996
DOI: 10.1111/j.1471-0528.1996.tb09742.x
|View full text |Cite
|
Sign up to set email alerts
|

The suitability of DNA cytometry for the prediction of the histological diagnosis in women with abnormal cervical smears

Abstract: Objective To analyse the suitability of DNA cytometry for predicting the histological diagnosis in Design Survey with the use of diagnostic information to revise disease probability.Setting Colposcopy clinic of a university hospital.Participants One hundred and ten women with two mildly or moderately dyskaryotic cervical smears and 98 women with one severely dyskaryotic smear.Interventions DNA cytometric analysis using cytocentrifuge preparations of single cell suspensions from a cervical scrape. The main DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…A recent study of the DNA-cytometric feature N5C (the absolute number of cells with DNA content of more than 5c) of patients with cervical neoplasia showed that the N5C values significantly increased with increasing severity of CIN grade. However, the N5C values could not discriminate between the two groups: (1) CIN II or more, and (2) CIN I or less [30]. These findings are in agreement with our previous results which showed that the 2.5c exceeding rate (ER) increased with increasing severity of the lesion [12].…”
Section: Discussionsupporting
confidence: 90%
“…A recent study of the DNA-cytometric feature N5C (the absolute number of cells with DNA content of more than 5c) of patients with cervical neoplasia showed that the N5C values significantly increased with increasing severity of CIN grade. However, the N5C values could not discriminate between the two groups: (1) CIN II or more, and (2) CIN I or less [30]. These findings are in agreement with our previous results which showed that the 2.5c exceeding rate (ER) increased with increasing severity of the lesion [12].…”
Section: Discussionsupporting
confidence: 90%
“…20,21 In addition, some investigators have suggested DNA cytometry is useful in equivocal cases, and here the goal is to differentiate between florid reactive inflammatory changes and true neoplasia. 22 A nondiploid state is known to correlate with the presence of carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution DNA-flow cytometry is known to be able to detect stem-cell lines with mutated DNA (21). Using DNA flow cytometry (22) and DNA image cytometry (23), a significant correlation between aneuploidy and grade of CIN has been shown. Even morphologically normal squamous epithelium adjacent to high-grade cervical intraepithelial neoplasia does not seem to contain any aneuploid cells (24).…”
Section: Discussionmentioning
confidence: 99%